Properties and Applications of Biodegradable Polymers - Patwary, M.A. Sayed; Surid, S.M.; Gafur, M.A. (Journal of Research Updates in Polymer Science, 2020)
Biodegradable materials are one of the major discussable matters in the modern world. To keep and produce environment-friendly products for our daily usage the utilization of degradable materials is increasing at a high rate. The modern world wants sustainable products which will not bring about any harm to the environment. Products made from plastics are sustainable but they cause great harm to our environment due to lack of degradation property. After the end of our usage, these materials can sustain for a long time without any degradation which causes a supreme level of loss to our environment. But if we can produce products by using biodegradable raw materials, they will be degraded by the action of bio-organisms hence our environment will be protected from a great loss. So, it has become a crying need for us to use biodegradable raw materials in our products. The materials which are not biodegradable cause a great pollution especially soil pollution. To protect the world from the cruel humiliation of waste, it has become an overwhelming necessity to manufacture biodegradable products, which can quickly be degraded in the environment, from our daily useable items. The materials contain almost all the properties which are suitable for our environment. Already these materials have been using in several sectors and showing their applications for their friendly properties.